Are precariousness and temporality the main characteristics of the youth employment in Spain? - Ma.Jesús Gómez Adillón; Ma.Àngels Cabasés Piqué; Agnès Pardell Veà (European Regional Science Association (ERSA), 2015)
In Spain the rate of youth unemployment has exponentially increased in the past few years, and it has turned into a structural problem. When the fourth quarter of 2014 ended, the destruction of employment, which begun along with the economic and financial crisis in 2008, has specially affected young people so that, among the people under the age of 30, the number of unemployed people was 1.495.600, 645.000 more than in the first quarter of 2008. Nevertheless, before 2008, the youth unemployment rate was already reaching 17,4% and some studies were alerting of the vulnerability of the above mentioned group of people, especially in the following areas: labour, education, residential and reproductive. Moreover, in this period of time, the employment policy has been affected, with no doubt, by the labour reform of 2012 (RDL3 / 2012 and Law 3/2012), by introducing new rules on the mediation in the labour market (Article 16.3 the Workers' Statute (ET)), the vocational training and new contractual modalities, specially modifying the ?contract for training and learning? (Article 11 ET), the modification of the part-time contract (Article 12 ET) and the distance contract (formerly called ?working at home contract?, Article 13 ET) and the introduction of a new indefinite contract called 'support to entrepreneurs'. These reforms have gone in the opposite direction to strengthen employment policies aimed to achieve the right to work or full employment for young people, law and constitutional mandate that in times of crisis are likely to disappear or be completely isolated. Labour statistics are one of the indicators that best express the economic and social reality of a country. Through the ?Muestra Contínua de Vidas Laborales? (MCVL) 2013, the career path between 2008 and 2013 of young people under 30 years is analysed, in order to determine changes and characteristics of their connection to the labour market. The research work shows that, between 2008 and 2013, most of the contracts signed with young people under 35 years were temporary and low paid. At the end of 2014, 78% of this group worked in the private sector, 46% with temporary contracts of which 36.6% for ?labour and service?, one in five young people did it part-time and one in ten with a temporary part-time contract. With micro data from the EPA, related to the fourth quarter of 2014, it is observed through two Logit models, how a low level of education and the sector of activity increase the likelihood that a young person under 34 years on the one hand, becomes unemployed and secondly, occupied by a temporary contract.
Keywords: J01; J21; J13; 330; youth employment; job insecurity and education